2011
DOI: 10.1016/j.psychres.2010.04.052
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial background in incarcerated adolescents from Austria, Turkey and former Yugoslavia

Abstract: Adolescents with migration background account for a substantial proportion of juveniles in custody. Psychosocial adversities pose a significant risk for criminal behavior. So far, the nature of psychosocial adversities experienced by migrant youth is understudied. The aim of this study was to explore differences in psychosocial background in three ethnic groups

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 50 publications
1
14
0
5
Order By: Relevance
“…This dimension may refer to antisocial and delinquent attitudes in JSO. In agreement with a general strain theory of crime (Agnew, 1992(Agnew, , 2005, psychosocial adversities like migration and subsequent cultural adjustment can be seen as chronic stressors, which have an impact on the development of general and sexual delinquency (Bauer et al, 2011;Erickson, Crosnoe, & Dornbusch, 2000). Familial problems and alcohol use in older JSO may reflect another dimension of sexual abusive behavior.…”
Section: Discussionmentioning
confidence: 77%
“…This dimension may refer to antisocial and delinquent attitudes in JSO. In agreement with a general strain theory of crime (Agnew, 1992(Agnew, , 2005, psychosocial adversities like migration and subsequent cultural adjustment can be seen as chronic stressors, which have an impact on the development of general and sexual delinquency (Bauer et al, 2011;Erickson, Crosnoe, & Dornbusch, 2000). Familial problems and alcohol use in older JSO may reflect another dimension of sexual abusive behavior.…”
Section: Discussionmentioning
confidence: 77%
“…Besides common indicators of juvenile delinquent and risk behaviors, such as low socio-economic status (SES) and age (e.g., DeLisi, Neppl, Lohman, Vaughn, & Shook, 2013;Kipping, Smith, Heron, Hickman, & Campbell, 2015), we added foreign nationality as a covariate because Switzerland has been shown to have high rates of migration, and previous research indicated that juveniles with foreign nationalities were overrepresented in the Swiss justice system (Killias, 2009). Moreover, further European studies showed that JSOs with foreign nationalities differed from domestic adolescent delinquents in regard to social and health adversities (e.g., Aebi et al, 2012;Bauer et al, 2011;Colins et al, 2013).…”
Section: Patterns Of Adverse Childhood Experiencesmentioning
confidence: 99%
“…34 Literature data on the influence of ethnic differences in this context are however inconsistent. Some studies reported less psychopathology in immigrant incarcerated youths compared to native ones.…”
Section: Young Detainees' Mental Health Profilementioning
confidence: 99%